High-Risk HPV16 E6 Activates the cGMP/PKG Pathway Through Glycosyltransferase ST6GAL1 in Cervical Cancer Cells - Wang, Jun; Liu, Gao; Liu, Mei; Cai, Qinzhen; Yao, Cong; Chen, Hao; Song, Neng; Yuan, Chunhui; Tan, Decai; Hu, Yuhai; Xiang, Yun; Xiang, Tian (Frontiers in Oncology, 2021)
Alterations in glycosylation regulate fundamental molecular and cellular processes of cancer, serving as important biomarkers and therapeutic targets. However, the potential association and regulatory mechanisms of E6 oncoprotein on glycosylation of cervical cancer cells still unclear. Here, we evaluated the glycomic changes via using Lectin microarray and determined the corresponding enzymes associated with endogenous high-risk HPV16 E6 expression in cervical cancer cells. α2-6 sialic acids and the corresponding glycosyltransferase ST6GAL1 were significantly increased in E6 stable-expressing HPV- cervical cancer C33A cells. Clinical validation further showed that the expression of ST6GAL1 was significantly increased in patients infected with high-risk HPV subtypes and showed a positive association with E6 in cervical scraping samples. Interfering ST6GAL1 expression markedly blocked the oncogenic effects of E6 on colony formulation, proliferation and metastasis. And importantly, ST6GAL1 overexpression enhanced tumorigenic activities of both E6 positive and negative cells. Mechanistical investigations revealed that E6 depended on activating YAP1 to stimulate ST6GAL1 expression, as verteporfin (inhibitor of YAP1) significantly suppressed the E6-induced ST6GAL1 upregulation. E6/ST6GAL1 triggered the activation of downstream cGMP/PKG signaling pathway and ODQ (inhibitor of GMP production) simultaneously suppressed the oncogenic activities of both E6 and ST6GAL1 in cervical cancer cells. Taken together, these findings indicate that ST6GAL1 is an important mediator for oncogenic E6 protein to activate the downstream cGMP/PKG signaling pathway, which represent a novel molecular mechanism and potential therapeutic targets for cervical cancer.